Content validity of the EORTC quality of life questionnaire QLQ-C30 for use in cancer. (January 2023) - Cocks, Kim; Wells, Jane R.; Johnson, Colin; Schmidt, Heike; Koller, Michael; Oerlemans, Simone; Velikova, Galina; Pinto, Monica; Tomaszewski, Krzysztof A.; Aaronson, Neil K.; Exall, Elizabeth; Finbow, Chelsea; et al.
Abstract: Aim: The European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (QLQ-C30) is among the most widely used patient-reported outcome measures in cancer research and practice. It was developed prior to guidance that content should be established directly from patients to confirm it measures concepts of interest and is appropriate and comprehensive for the intended population. This study evaluated the content validity of the QLQ-C30 for use with cancer patients. Methods: Adults undergoing cancer treatment in Europe and the USA participated in open-ended concept elicitation interviews regarding their functional health, symptoms, side-effects and impacts on health-related quality of life. Thematic analysis was conducted, and similarities across cancer types, disease stages and countries or languages were explored. Results: Interviews with 113 patients with cancer (85 European, 28 USA) including breast, lung, prostate, colorectal and other cancers were conducted between 2016 and 2020. Conceptual saturation was achieved. The most frequently reported concepts were included in the QLQ-C30 conceptual framework. QLQ-C30 items were widely understood across language versions and were relevant to patients across cancer types and disease stages. While several new concepts were elicited such as difficulty climbing steps or stairs, weight loss, skin problems and numbness, many were not widely experienced and/or could be considered sub-concepts of existing concepts. Conclusions: The QLQ-C30 demonstrates good evidence of content validity for the assessment of functional health, symptom burden and health-related quality of life in patients with localised-to-advanced cancer. Highlights: European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 is widely used to measure quality of life in oncology. Content validity is evidence that an instrument measures the concept of interest. Measures should demonstrate content validity directly from patients. This study demonstrates content validity across a broad range of cancers and stages. The European Organisation for Research and Treatment of Cancer measurement model remains valid today for use in research.